THE ROLE OF TEACHING LISTENING COMPREHENSION IN THE NEW NORMAL ERA - Novianty, Melisa (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2020)
Listening Comprehension is a process to know about what the speakers talk about to get some information and knowledge. The purpose of this study was to know how and why the students learn listening skill in the new normal era. In fact, there were some problems faced to the students as long as they learn and work from home. For examples, they don’t have mobile phone, andno internet access for communication. Therefore, the teacher should more creative to teach the students, especially in learning listening comprehension. In this study, the roles of learning listening would be discussed with some various ways from the simple to the complete one. Hopefully, all of them could help the students to learn easyly, and then the teacher could improve their ways to teach the students by following the rules in this study.